Porphyrin–Nanodiamond Hybrid Materials—Active, Stable and Reusable Cyclohexene Oxidation Catalysts - Dias, Lucas Danilo (2020)
The quest for active, yet “green” non-toxic catalysts is a continuous challenge. In this work, covalently linked hybrid porphyrin–nanodiamonds were prepared via ipso nitro substitution reaction and characterized by X-ray photoelectron spectroscopy (XPS), fluorescence spectroscopy, infrared spectroscopy (IR) and thermogravimetry-differential scanning calorimetry (TG-DSC). The amine-functionalized nanodiamonds (ND@NH2) and 2-nitro-5,10,15,20-tetra(4-trifluoromethylphenyl)porphyrin covalently linked to nanodiamonds (ND@ NH-TPPpCF3) were tested using Allium cepa as a plant model, and showed neither phytotoxicity nor cytotoxicity. The hybrid nanodiamond–copper(II)–porphyrin material ND@ NH-TPPpCF3-Cu(II) was also evaluated as a reusable catalyst in cyclohexene allylic oxidation, and displayed a remarkable turnover number (TON) value of 265,000, using O2 as green oxidant, in the total absence of sacrificial additives, which is the highest activity ever reported for said allylic oxidation. Additionally, ND@ NH-TPPpCF3-Cu(II) could be easily separated from the reaction mixture by centrifugation, and reused in three consecutive catalytic cycles without major loss of activity.